The Impact of Farmer Field Schools (SLK) Program Implementation on the Cocoa Farm Business in Lima Puluh Kota Regency - Walmadri, Walmadri; Hasnah, Hasnah; Tanjung, Faidil (International Journal of Environment, Agriculture and Biotechnology, 2019)
Cocoa industry in West Sumatra has high potential to increase the income of small farmers. However, cocoa production is still below production potential. The implementation of the cocoa field school program (SLK) is one of approaches to develop cocoa farm business. This field school is expected to improve the performance of smallholders’ cocoa farming, both in terms of production and quality. To assess the extent to which this field school has helped farmers to increase their capacity to manage cocoa farming, research is needed to analyze the impact of the implementation of the farmer field school program on cocoa farming as measured by level of technology adoption and economic impact by comparing cocoa income between participant and non-participant farmers in farmer field school program. The study was conducted in Lima Puluh Kota Regency which involved a sample of 80 people, consisting of 40 SLK farmers and 40 non-SLK participants. The results showed that forthe impact of the SLK on cocoa farming, it was found thatfor the price variable there was a significant difference but for the variable production, farming costs and income between farmers and non-SLK participants there were no significant differences. In conclusion that the cocoa field school program has not significantly affected cocoa farming practices in Lima Puluh Kota. As a result, the expected increase in production and quality of cocoa has not been achieved.